PENGGUNAAN APRIORI PADA REKOMENDASI PAKET MENU DAN DILENGKAPI FITUR CHATBOT - Yosua Pandapotan Sianipar; Viny Christanti Mawardi; Tri Sutrisno (Fakultas Teknologi Informasi Universitas Tarumanagara, 2022)
The growth of the food and beverage industry is the pillar of national and manufacturing economic growth. At present the food and beverage sector continues to be excellent, especially in the tourism industry sector which develops culinary tourism. In the sale of food and beverages in the world of tourism, it is made to attract the attention of consumers by making promotional packages. This promotional package aims to attract buyers to want to buy products from a restaurant. One way to make a promotion is by using association rules. Association rules are the results that will issue a combination of numbers from each transaction data. This was done to help increase the sales of Ling Ling Restaurant. To find the results of association rules whose combinations are used for promotion, here we use the Apriori method. The results that come out will be in the form of a food or drink menu that has been combined into two, three, or more according to the number of association rules that came out by going through the Apriori method. The results of the association rules that come out later will be displayed on the chatbot display contained in the program. The chatbot here will display the results of the association rules obtained using the Apriori method and also display several question options using questions that have been created in the chatbot.